2014
DOI: 10.1007/s00723-014-0584-9
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Majorana Quasiparticles’ Edge States in Superfluid 3He

Abstract: We suggest in this article the nuclear magnetic resonance (NMR) method of observation and investigations of Majorana fermions at the edge of Topological Insulator, superfluid 3 He-B. The Majorana fermions form the remarkable quantum state of condensed matter where particle-like and antiparticle (holelike) excitations are indistinguishable. They have been observed recently by deviation of the temperature dependence of the superfluid 3 He-B heat capacity from the well-known exponential law for Bogoliubov quasipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Recent transverse acoustic impedance measurements with an well-controlled surface condition succeeded in the spectroscopy of surface bound states, which captured the surface density of states peculiar to the Majorana cone. 58) The characteristics of the Majorana cone were also observed in the heat capacity measurement by Bunkov et al 53,54) In addition, SQUID-NMR experiments reported the observation of the' z domain wall. 44) These experimental observations are the first step to further capturing a hallmark of chiral and helical Majorana fermions.…”
Section: Summary and Prospectsmentioning
confidence: 77%
See 3 more Smart Citations
“…Recent transverse acoustic impedance measurements with an well-controlled surface condition succeeded in the spectroscopy of surface bound states, which captured the surface density of states peculiar to the Majorana cone. 58) The characteristics of the Majorana cone were also observed in the heat capacity measurement by Bunkov et al 53,54) In addition, SQUID-NMR experiments reported the observation of the' z domain wall. 44) These experimental observations are the first step to further capturing a hallmark of chiral and helical Majorana fermions.…”
Section: Summary and Prospectsmentioning
confidence: 77%
“…[52][53][54] In Ref. 52, they reported the clear deviation of CðTÞ from that of the bulk 3 He-B in the vicinity of T c , which is attributed to the sufficient zero-energy density of states at the diffusive surface.…”
Section: Observations Of Surface Bound States In 3 He-bmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them one can note classical magnon dynamics effects like parametrically stimulated recovery of a microwave signal, [1,2] magnon wavefront reversal, [3,4] magnetic solitons [5,6] and two-dimensional spin-wave bullets, [7,8] strain-induced magnon effects, [9] nonreciprocity and transformation of spin waves in ferromagnetic-semiconductor and ferromagnetic-multiferroic structures, [10,11] and many others. Simultaneously, novel quantum macroscopic collective phenomena, such as Bose-Einstein condensation (BEC) of magnons, [12][13][14][15] magnon vortices [16] and supercurrents, [17][18][19] as well as a space-time crystal in the magnon BEC [20] open new directions for the utilization of the magnon system. The large variety of the effects in magnon systems is observed due to the manifold of multi-magnon scattering processes in combination with the inherent nonlinearity in a magnetic medium.…”
Section: Introductionmentioning
confidence: 99%